Finite element analysis of the PreWEC self-centering concrete wall system. (15th May 2016) - Henry, R.S.; Sritharan, S.; Ingham, J.M.
Highlights: A finite element model was developed for a self-centering precast concrete wall system. The model accurately captured the cyclic lateral-load response of a test wall. Energy dissipating connectors can be added to the system without altering the wall axial load. Wall axial load ratios should be kept below 10% to avoid significant toe damage. Wall-to-floor connection design is critical to the building lateral-load response. Abstract: A self-centering concrete wall system has been developed that consists of a Precast Wall with End Columns (PreWEC). A finite element model was developed to investigate the cyclic lateral-load response of the PreWEC system that included allowance for uplift at the wall-to-foundation interface, inclusion of the energy dissipating O-connectors, and inelastic behaviour of the confined concrete in the toe of the wall. The model showed good correlation with the results of a large-scale experimental test of the PreWEC system for both the global and local responses, closely matched the experimental lateral force–displacement response, unbonded tendon stress, neutral axis depth, concrete compressive strains, and connector deformation. Additional analyses were conducted to investigate modifications to the PreWEC design. These modified designs highlighted the influence of the inelastic behaviour of the wall toe and showed that in the PreWEC system the axial load on the wall panel is independent of the number of energy dissipating connectors. Lastly, analyses were conducted to investigate wall-to-floor interaction with the PreWEC system. It was shown that a rigid wall-to-floor connection would result in some damage to the floor diaphragms and an overstrength that should be considered when designing the wall for shear. Alternatively, connectors could be used with the PreWEC system to isolate the floor from the uplift of the wall and eliminate damage to the floor diaphragm.